2022
DOI: 10.1128/spectrum.01505-21
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid Fusion and Recombination Events That Occurred during Conjugation of poxtA -Carrying Plasmids in Enterococci

Abstract: Until now, all the poxtA genes described in enterococci, including E. faecalis , E. faecium , and E. hirae , are plasmid-borne, suggesting that plasmids play an important role in the dissemination of the poxtA gene among enterococci. This study showed that the mobilizable poxtA -carrying plasmid could transfer with the help of conjugative plasmid in enterococci via pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…It is reported that ISs participate in 63.2% of the transferred AMR genes between plasmids and chromosomes ( 24 ). For instance, IS 26 and IS 1216E (IS 6 family) could mediate plasmid fusion and transmit resistance-encoding genes ( 25 , 31 ). Besides, replicative transpositions were reported in other presumed MGEs, such as Tn 4401 (Tn 3 family), IS 903B (IS 5 family), and IS Kpn14 (IS 1 family) ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that ISs participate in 63.2% of the transferred AMR genes between plasmids and chromosomes ( 24 ). For instance, IS 26 and IS 1216E (IS 6 family) could mediate plasmid fusion and transmit resistance-encoding genes ( 25 , 31 ). Besides, replicative transpositions were reported in other presumed MGEs, such as Tn 4401 (Tn 3 family), IS 903B (IS 5 family), and IS Kpn14 (IS 1 family) ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…These strains were isolated from environmental (pF88_1) and human samples (p17-318_1 and pE843-TC-299). The fourth plasmid, pE843-171, is carried by Enterococcus lactis E843, and it is characterized as VSE-MDR (Shan et al, 2022 ). According to these results, pUC7251_1 holds unique traits, and although the prevalence of VSE-MDR is high, none of the results on BLAST showed VSE-MDR from food origin.…”
Section: Resultsmentioning
confidence: 99%
“…Formation of larger cointegrates, likely with an involvement of very ubiquitous IS 1216 , might explain the existence of larger, approximately 170 kb plasmids hybridizing with the vanA probe, apart from the main 21.6 kb form of the vanA- plasmid. Formation of such fusions was indeed demonstrated for larger conjugative plasmids and smaller mobilizable poxtA- plasmids, enabling transfer of linezolid resistance from E. faecalis and Enterococcus lactis [ 62 ]. The majority of repUS1 pVEF1 - vanA plasmids represented multireplicons, which contained also rep18a , located upstream Tn 1546 and in some instances repUS1 pVEF1 - vanA plasmids carried also rep1, rep2 and/or rep9 .…”
Section: Discussionmentioning
confidence: 99%